2008
DOI: 10.5739/isfp.2008.47
|View full text |Cite
|
Sign up to set email alerts
|

Design and Fuel Economy of a Series Hydraulic Hybrid Vehicle

Abstract: A series hydraulic hybrid drive train for application in a passenger car is described. This 'Hydrid' drive train features an in-wheel hydraulic motor in all four wheels, hydraulic transformers for power control and hydraulic-pneumatic accumulators for energy storage and power management. The hydrostatic components are based on the highly efficient floating cup principle. The result is an efficient all-wheel drive vehicle with variable traction control on the front and rear axis. The fuel economy and the CO2-em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…In recent years, literatures reported that filament winding technology was used to manufacture the shell of accumulator in order to reduce the shell weight and improve the power density greatly, the shell weight used new technology was only half or even 10% of that in traditional hydraulic accumulator, however, this accumulator has not reached the stage of project application yet [31]. Peter Achten mentioned the opinion of combining the battery having the advantage of high energy density with hydraulic accumulator in hybrid power vehicles in literature [32]. Fig.…”
Section: B the Development And Selection Of Energy-storage Componentmentioning
confidence: 99%
“…In recent years, literatures reported that filament winding technology was used to manufacture the shell of accumulator in order to reduce the shell weight and improve the power density greatly, the shell weight used new technology was only half or even 10% of that in traditional hydraulic accumulator, however, this accumulator has not reached the stage of project application yet [31]. Peter Achten mentioned the opinion of combining the battery having the advantage of high energy density with hydraulic accumulator in hybrid power vehicles in literature [32]. Fig.…”
Section: B the Development And Selection Of Energy-storage Componentmentioning
confidence: 99%
“…There are a number of literatures focusing on energy-saving control strategy of HHV and structural design and characteristics test of HT. [10][11][12][13] However, the publications devoted to pulsating characteristic of HHV with pipeline effect are relatively scarce.…”
Section: Introductionmentioning
confidence: 99%
“…At the moment, many types of research focus on the simulation of the fuel consumption in the hybrid passenger car [19] [20][8] [21]. Nonetheless, a few only carrying out the detailed research related to the subsystem itself.…”
Section: Introductionmentioning
confidence: 99%